2008
DOI: 10.3181/0803-rm-93
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract ofCuminum cyminumInhibits Ovariectomy-Induced Bone Loss in Rats

Abstract: Several animal and clinical studies have shown that phytoestrogens, plant-derived estrogenic compounds, can be useful in treating postmenopausal osteoporosis. Phytoestrogens and phytoestrogen-containing plants are currently under active investigation for their role in estrogen-related disorders. The present study deals with anti-osteoporotic evaluation of phytoestrogen-rich plant Cuminum cyminum, commonly known as cumin. Adult Sprague-Dawley rats were bilaterally ovariectomized (OVX) and randomly assigned to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…HPTLC technique with other biochemical assays supplemented evidence to confirm the presence of some bioactive compounds, which have provided the plants an important position in folkloric usage [15] In the present study, quantitative and qualitative biochemical methods can be employed as a stability indicator [16] that can be used for the routine quality control analysis and quantitative determination of β-sitosterol from Lepidium sativum. Results obtained by HPTLC for diazdzein and formononetin were coincided with the results of [17][18][19]. Although originally identified in cementum, PTPLa/ CAP is very effective at inducing bone repair and healing and therefore this novel molecule has a great potential to be used for mineralized tissue bioengineering and tissue regeneration studied by [20].…”
Section: Discussionsupporting
confidence: 66%
“…HPTLC technique with other biochemical assays supplemented evidence to confirm the presence of some bioactive compounds, which have provided the plants an important position in folkloric usage [15] In the present study, quantitative and qualitative biochemical methods can be employed as a stability indicator [16] that can be used for the routine quality control analysis and quantitative determination of β-sitosterol from Lepidium sativum. Results obtained by HPTLC for diazdzein and formononetin were coincided with the results of [17][18][19]. Although originally identified in cementum, PTPLa/ CAP is very effective at inducing bone repair and healing and therefore this novel molecule has a great potential to be used for mineralized tissue bioengineering and tissue regeneration studied by [20].…”
Section: Discussionsupporting
confidence: 66%
“…cyminum essential oil at dose levels of 250,500 and 1000 mg/ day was orally administered to female mice for 14 days caused marked elevation in the body weight , uterus and estradiol levels(p<0.001) whereas the progesterone levels were decreased significantly in all dose groups including 25 mg/kg after 28 days study (p=0.001) . Phytoestrogen properties of cumin extract has been previously described (25)and it was identified useful in treating postmenopausal osteoporosis and estrogen-related disorders in bilaterally ovariectomized rat as an osteoprotective product comparable with estradiol (26).This study suggests the phyotoestrogenic effects of cumin essential oil which should be confirmed by later studies using specific models. On the other side, another study showed a marked reduction in sperm density in the cauda epididymis and testes and sperm motility in the cauda epididymis as well as fertility reduction, significant decreases in the number of testicular cells, secondary spermatocytes and round spermatids (27) with its endocrine disruptive effects.…”
Section: Discussionsupporting
confidence: 61%
“…Basu et al (2001) revealed that the osteoporosis could be eliminated when oxidative stress is prevented. Unfortunately, the current pharmacological therapy used for treatment of osteoporosis have serious adverse effects besides its inability to restore lost bone mass (Shirke et al, 2008). Bisphosphonates administration is widely used for management of osteoporosis.…”
Section: Introductionmentioning
confidence: 99%